Alignment in Syntax: Quotative Inversion in English. (15th April 2016) - Bruening, Benjamin
Abstract: This paper explores the idea that many languages have a phonological Align(ment) constraint that requires alignment between the tensed verb and C. This Align constraint is what is behind verb‐second and many types of inversion phenomena generally. Numerous facts about English subject–auxiliary inversion and French stylistic inversion fall out from the way this Align constraint is stated in each language. The paper arrives at the Align constraint by way of a detailed reexamination of English quotative inversion. The syntactic literature has overwhelmingly accepted Collins & Branigan's (1997) conclusion that the subject in quotative inversion is low, within the VP. This paper reexamines the properties of quotative inversion and shows that Collins & Branigan's analysis is incorrect: quotative‐inversion subjects are high, in Spec, TP, and what moves is a full phrase, not just the verb. The constraints on quotative inversion, including the famous transitivity constraint, fall out from two independently necessary constraints: (1) a constraint on what can be stranded by phrasal movement like VP fronting, and (2) the aforementioned Align constraint, which requires alignment between V and C. This constraint can then be seen to derive numerous seemingly unrelated facts in a single language, as well as across languages.